Niveles de resiliencia en docentes de inicial, primaria y secundaria de la Región Callao - Guerra La Torre, José Luis (2010)
Were compared, the levels of resilience in teachers of initial, primary and secondary Callao Region. The test called the scale of teacher resilience (ER-D) was designed from the six factors that construct resilience at school proposed by Henderson and Milstein. With 71 items the pilot test was administered to 710 public school teachers in Callao Region and submitted to a study to determine its reliability and construct validation. It was concluded that yes there are significant differences in the levels of resilience among teachers of initial, primary and secondary and that the ER-D is a valid and reliable instrument to measure resilience in teachers. It also showed that teachers of initial are more resilient than others.